(untitled) (American Journal of Life Science and Innovation, 2024)
The educational process in any society constitutes an accumulation of knowledge resulting from the succession of times according to the ideologies of that society, taking into account its cognitive developments and the challenges it faces to defend its values and beliefs, through the development of promising educational programs that keep pace with the development of the present to assume its future status according to its glorious legacy, and to preserve this accumulation of knowledge across generations, the supervision and evaluation apparatus at the Iraqi Ministry of Education constitutes its main task to evaluate the educational process and provide appropriate solutions to develop performance in the educational institution and for all scientific disciplines, including these specializations (supervisors of the specialization of Physical Education) who are responsible for The task of evaluating the sports educational process in Iraq at the educational, administrative and technical levels within the educational institution. The research problem started from what is the temporal orientation of the supervisors of the specialization of physical education in Baghdad so that we can evaluate their performance present and future in a way that suits the developments of society and achieve its goals, and the aim of the current research is to identify the temporal orientation of the supervisors of the specialization of physical education in Baghdad, so it was necessary to build a measure of temporal orientation in the Iraqi sports education environment first, the researcher has tested the significance of differences between the arithmetic averages of the temporal orientation of the research sample between (Past, Present and future) and the field research data revealed that there are significant differences in favor of both (past, present and Future) Present and future), which indicates the temporal direction of the examined sample towards The researcher recommended that supervisors should be educated on the subject of temporal orientation, and the process of linking these three eras (past – present – future) in constructive interaction with life to develop educational institutions, being directly responsible for evaluating the educational process in the field of sports activities.